Cajamarca and the impact of Minera Yanacocha - Alfaro Montoya, Kely (2006)
This article is an attempt to analyze the reality of Cajamarca since the arrival of Minera Yanacocha; Based on real data, departmental growth, urban perspectives and new responsibilities are examined.